The Relations of Tutor Teaching Performance and Science Learning Outcome of Learners at Paket B Equivalency Program - Sania Kasih Mukhlis; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is motivated by the low learning outcomes of residents learning equivalence Package B at SPNF Pasaman Regency, this is thought to be due to the influence of tutor performance in learning of science subjects for class VIII. This study aims to: 1) describe the performance of tutors; 2) describe the learning outcomes of learning citizens; and 3) looking at the relationship between tutor performance in learning and learning outcomes in Science Class VIII Equivalence Package B at SPNF Pasaman Regency. This type of research is quantitative research with correlational descriptive technique. The population of this study were all students of class VIII Package B Program at SPNF Pasaman Regency, totaling 180 people and with a sample of 44 people. The data collection technique is in the form of a questionnaire with a data collection tool in the form of a questionnaire and the data is analyzed using the percentage technique and product moment correlation. The results showed that: (1) the performance of tutors in  learning of science subjects for class VIII was categorized as low, (2) the learning outcomes of students were categorized as low, (3) there was a significant relationship between the performance of tutors in  learning and science learning outcomes. class VIII Equality Package B at SPNF Pasaman Regency. It is recommended for institutions to pay more attention to the performance of tutors, and it is hoped that tutors can improve performance in learning.